2002
DOI: 10.1007/s11926-002-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in patients with inflammatory myopathy

Abstract: The most recent evidence from population-based cohort studies confirms the association between malignancy and dermatomyositis and polymyositis. These studies show an even stronger association between polymyositis and malignancy than previous studies, suggesting less misclassification. This is particularly true of one study that used pathologic criteria to distinguish between myositis subtypes. Recent data also confirm that the association for dermatomyositis and polymyositis is not purely caused by diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 54 publications
(63 reference statements)
1
42
0
10
Order By: Relevance
“…Patients with DM have an inherent increased risk of malignancy, mostly solid tumors, (eg, ovarian, gastrointestinal, and pulmonary) that are usually discovered within the first 3 years following diagnosis. [8][9][10][11][12]14,[30][31][32][33][34] In multiple population-based studies of rheumatic diseases including DM and rheumatoid arthritis, an increased risk for B-cell lymphoma of the CNS has not been demonstrated. [8][9][10][11][12][30][31][32]34 In contrast, a number of malignancies associated with immunosuppressive therapy are lymphoma or leukemia and are similar to those observed in other immunosuppressed states, such as AIDS and organ donor recipients on immunosuppressive therapies in whom extra-nodal large B-cell lymphomas predominate and tend to contain EBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with DM have an inherent increased risk of malignancy, mostly solid tumors, (eg, ovarian, gastrointestinal, and pulmonary) that are usually discovered within the first 3 years following diagnosis. [8][9][10][11][12]14,[30][31][32][33][34] In multiple population-based studies of rheumatic diseases including DM and rheumatoid arthritis, an increased risk for B-cell lymphoma of the CNS has not been demonstrated. [8][9][10][11][12][30][31][32]34 In contrast, a number of malignancies associated with immunosuppressive therapy are lymphoma or leukemia and are similar to those observed in other immunosuppressed states, such as AIDS and organ donor recipients on immunosuppressive therapies in whom extra-nodal large B-cell lymphomas predominate and tend to contain EBV.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatomyositis (DM) is associated with cancer, especially ovarian cancer in women. [8][9][10][11][12] Although malignancy can develop after the diagnosis of dermatomyositis, there is little evidence that the use of immunosuppressive therapy to treat this condition is associated with the development of subsequent neoplasia. 4,6,[12][13][14][15][16][17][18][19] We present a patient with DM treated with immunosuppressive therapy for 5 years who developed an EBV-associated B-cell lymphoma of the CNS.…”
mentioning
confidence: 99%
“…Additionally, the Bohan and Peter criteria, which do not take into account histological differences between PM, DM, and IBM, may have limitations in their specificity to properly diagnose and classify the different forms of IIM [21,22]. Cohort studies performed in Australia by Buchbinder et al [23,24], and more recently by Limaye et al [13], have attempted to correct for this by defining myositis subtypes based on well-recognized modern muscle biopsy criteria.…”
Section: Epidemiologymentioning
confidence: 99%
“…In 2002, a population-based cohort study based in Australia [23,24] confirmed an increased risk for malignancy in 537 patients with DM, PM, and IBM, with SIRs of 6.2, 2.0, and 1.8, respectively. One advantage of this study was that the population was identified based on muscle biopsy features.…”
Section: Epidemiologymentioning
confidence: 99%
“…The association of dermatomyositis (DM) with malignancy was first reported in 1916 but only confirmed with more recent large, population-based, retrospective cohort studies [1,2]. Patients with polymyositis (PM) may also have an associated malignancy, but the risk is lower than that for DM patients.…”
Section: Introductionmentioning
confidence: 99%